Student Leader and Dynamics of Campus Life (Open Society Conference, 2023)
This paper discusses student leaders, an interesting question is "What is an ideal student leader?" This question is difficult to answer, because apart from the many criteria, the form or figure of an ideal student leader is only a reference. What is clear, students are a group in society with a "student-style" style and association, they must be able to think critically - systematically. In addition, youth and pioneering spirit must be stimulated to continue to move to find self-identity without giving up intellectual values and concern for social reality. So what is the figure of a student leader in the dynamics of campus life? The answer is, it doesn't need to be difficult because they already have some adaptations. Students are required to be democratic in dealing with various problems, especially in the dynamics of campus life. Students are personified as intellectuals who seek the truth.